Las diferencias del léxico español-lituano en la enseñanza de la lengua española y en la práctica lexicográfica - Rascón Caballero, Alfonso (Círculo de Lingüística Aplicada a la Comunicación, 2023)
In foreign language teaching and in lexicography practice it is far more important to consider the use of the word than the meaning; therefore, lexical pairs such as ciudad-miestas have to be avoided and the use of sentences and expressions has to be fostered. We cannot deny that word always works as a basic unity in the linguistic investigation. The speaker unconsciously creates links between each word and its meaning in his own language and when he learns other language continues to apply this link. Nevertheless teaching practice proves the perils that turn out when univocal links between word of a foreign language and its supposed meaning are established. Taking concrete uses of words (buenos días – laba diena, ranka – mano, brazo) as examples is quite clear that semantic structure of the word in one language does not coincide entirely with another. Comparing Spanish and Lithuanian vocabulary degrees of differentiation can be established: 1. almost direct equivalence between words (persona-žmogus, libro-knyga, trabajar-dirbti); 2. uncomplete equivalence of the meaning of the supposed translations (niño:1. vaikas, 2. berniukas; vaikas: 1. niño, 2. hijo). On the other hand in spanish there is a tendency to express with several words what in lithuanian is expressed with one: bijoti - tener miedo, sportuoti – hacer deporte. But the use of a word in specific sentences determines different lexical correspondences: atkreipk dėmesį – fíjate, nekreipk dėmesio – no hagas caso. Spanish is far more abstract than lithuanian: a word in Spanish corresponds to several in Lithuanian depending on the words it combines with, e.g. ponerse (la chaqueta) – apsiregnti (švarką), (el pantalón) – užsimauti (kelnes), (la gorra) – užsidėti (kepurę)... or on the way the action is done (llevar - vesti, vežti, nešti...). There are lithuanian words that have no lexical equivalence in Spanish (atsigrožėti, atsistebėti, atsidžiaugti), and viceversa (cariño, insistir), and they only can be translated in specific sentences. Good dictionaries provide a main translation for a headword when it is thought to be genuinely valid in a majority of contexts. Where it is not possible to give a main translation, illustrative examples are provided.